”I kamp og på flugt”. Om H. C. Andersens Den lille havfrue gendigtet som en beretning om handicap - Zańko, Aldona (Folia Scandinavica Posnaniensia, 2024)
The present paper offers a study of two contemporary English-language reworkings of Hans Christian Andersen’s fairy tale The Little Mermaid: one by the M. Sickafoose (1995) and one by A. Woon (2016), from the perspective of disability theory. In each of them, the original tale has been reframed into a story featuring a young girl striving to approach her inability to walk while drawing inspiration from the original tale. Due to their use of intertextuality, the texts to be analyzed are discussed as examples of the so-called postmodern fairy tale, aimed at interrogating the relevance of classic fairy tales through the act of retelling. In spite of similarities in terms of theme, plot outline and character construction, the versions selected for the analysis differ in terms of ending scenarios, offering two complementary messages concerning Andersen’s tale. While exploring the changes in the overall understanding of disability underlying the original and the two contemporary versions, the analysis aims to determine the potential of Andersen’s fairy tale as a possible frame of reference while confronting handicap in the social reality of the present era.